Analisis Keuntungan Pada Saluran Pemasaran Broiler Di Kota Ambon (Studi Kasus Pada UD. Elang Jaya Abadi) - Takimpo, Badarudin; Jesajas, Heriyanus; Matatula, Michel J.; Ririmase, Pieter M. (Jurnal Agrosilvopasture-Tech, 2024)
This study aims to determine the profit analysis on the marketing channel of broiler chickens in Ambon City (Case study on UD. Elang Jaya Abadi). This research was carried out from June 2021 to July 2021. This research was conducted in UD. Elang Jaya Abadi is located in the village of Laha. The research conducted is a case study research using the survey method. The results of this study can be concluded that the marketing channel of broiler chickens at UD. Eagle Jaya Abadi is a one-level distribution channel being direct marketing from Farmers-Tranders-Retailers-Consumers and profit margin on broiler chicken marketing channel owned by UD. Eagle Jaya Abadi is Rp 43,500 per period and at retailer lever of Rp 21,500 per period.